Can biogenic amines cause ailments following the intake of edible mushroom meals? - Eva Dadáková; Tamara Pelikánová; Pavla Wolfová; Pavel Kalač (Czech Journal of Food Sciences, 2022)
Several toxicological centres have reported ailments, mainly digestive inconveniences, following the intake of provably edible mushroom species. The causes of such complaints have not been explained yet. We, therefore, tested levels of biogenic amines (BAs). Fruit bodies of widely consumed wild-growing species, Imleria badia and Suillus variegatus were stewed, then preserved by freezing or canning and stored for up to 12 months. Contents of six amines were determined in the fresh matter, in each step of preservation and during storage. Histamine (HIM) and cadaverine (CAD) were not detected at all. Putrescine (PUT) occurred in fresh fruit bodies at levels of 700-1 500 mg kg-1 dry matter (DM), however, its contents considerably decreased, particularly during stewing. Undesirable phenylethylamine (PEA) and tyramine (TYM) occurred at lower levels. Stewing, the technological step necessary in both the tested preservation treatments, reduced the contents of all the amines alike as sterilisation, whereas following storage showed a limited effect. PUT seems to be the only amine that could participate in the reported ailments.